KEEFEKTIFAN TEKNIK SHOW NOT TELL TERHADAP KEMAMPUAN MENULIS RUPAMA SISWA KELAS 8 SMPN 26 MAKASSAR: The Effectiveness of Show Not Tell Technique on The Ability To Write Rupama of Grade 8 Smpn 26 Makassar Students - Aris Wahyudi, Muhammad; Hajrah; Yunus, Andi Fatimah (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research aims to: describe the ability of 8th-grade students at SMPN 26 Makassar in writing Rupama literature before using the show not tell technique; describe the ability of 8th-grade students at SMPN 26 Makassar in writing Rupama literature after using the show not tell technique, and; describe the effectiveness of the use of the show not tell technique in writing Rupama literature for 8th-grade students at SMPN 26 Makassar. This study is an Experimental Research. The research design is One Group Pretest Posttest. The variables in the study are the show not tell technique and the writing ability of Rupama literature for 8th-grade students at SMPN 26 Makassar. The research sample consists of students from the 8th grade at SMPN 26 Makassar. The data collection technique used is the initial test (pretest) and the final test (posttest). The data analysis technique includes descriptive statistical analysis, hypothesis testing, and graphs. The results of this research indicate that: the ability to write Rupama literature by students before using the show not tell technique is categorized as subpar, the ability to write Rupama literature by students after using the show not tell technique is categorized as sufficient, and the show not tell technique is not effective in improving the ability to write Rupama literature.